PHYSICOCHEMICAL ASSESSMENT OF VARATIKA (COWRIES) WITH DIFFERENT SHODHANA DRAVYAS DESCRIBED IN RASATARANGINI - SHIRKANDE, ANKITA INGOLE-; SHIRKANDE, ABHIJEET; THANVI, HARSHA; JADHAV, KALYANI; DALAVI, MADHURI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The present study entitled “Physicochemical Assessment of Varatika with Different Shodhana Dravyas Described In Rasatarangini” summarized briefly in Literary, pharmaceutical, Analytical and Experimental parts. To carry out literary review of Varatika and Shodhana Dravyas viz. Kulattha (Dolicus biflorus) and Nimbu (Citrus medica). To assess physicochemical properties of Ashodhita and Shodhita Varatika & the physicochemical changes in Shodhana Dravyas. It comprises the literatures on Varatika described classically in Rasa granthas and also modern information of Varatika (Cowrie). It also includes review on the associated Dravyas used for Shodhana viz. Kulatthakwatha and Nimbuswarasa. Pharmaceutical review reveals the concept of Shodhana, Swedana along with Dolayantra, used in present study. Analytical review includes Physico- Chemical Analytical methods like Total Ash Value, Acid Insoluble Ash, pH, Loss on Drying at 1100 C, XRD, FTIR, SEM-EDS and AAS were reviewed. According to XRD pattern, composition of Ashodhita Varatika (K) is CaCO3 confirmed by PDF# 41-1475 of JCPDS data. Sample K2 Shows some extra peaks, might be due to Shodhana Dravya. Trace amount of phosphorus is found in Kapardika Shodhita by method 1 which may prove helpful in therapeutics.